My hero academia. Vol. 9, My hero - Horikoshi, Kōhei, 1986- (Shonen Jump manga., 2017)
What would the world be like if 80 percent of the population manifested superpowers called "Quirks"? Heroes and villains would be battling it out everywhere! Being a hero would mean learning to use your power, but where would you go to study? The Hero Academy of course! But what would you do if you were one of the 20 percent who were born Quirkless? It's off to summer camp for Midoriya and the U.A. students! But this is no ordinary vacation--it's high-impact training where the students are expected to develop their Quirks even further! The teachers have set up some tough challenges, but none will be as difficult and as life changing as the threat a new group of enemies poses. What's even worse is who the villains' target is and why...